Instability of in situ TiC particles in an Al-12Si alloy - F. Xia; M.X. Liang; X.S. Gao; Y.C. Guo; J.P. Li; W. Yang; Z.K. Zhang (Journal of Materials Research and Technology, 2020)
This paper studied the evolution of in situ TiC particles in an Al-12Si alloy and the effect of Si on their stability. The samples were observed with scanning electron microscopy, and the phase analysis was performed by energy dispersive spectroscopy, X-ray diffraction, and transmission electron microscopy. The results demonstrated that Si can directly promote the evolution of TiC. After holding the TiC/Al-12Si alloy (TiC content of 2.75 wt.%) at 800 °C for 5 min, a large amount of TiC reacted with Al to form an Al4C3 phase and the Ti in TiC reacted with Al and Si to form a TiAlSi phase. When the holding time was increased to 20 min, the TiC almost completely disappeared. The morphology of TiC gradually changed from a regular tetra-decahedron to a sphere when Si was not added, and the average size gradually decreased from 1 μm and eventually disappeared completely. Si can diffuse into the TiC lattice to destroy its structure, thus forming a Si-rich disordered layer at the edge of the TiC particles. The values of diffusion resistance of Ti and C atoms in TiC, decrease owing to the destruction of the TiC lattice structure, which accelerates the TiC transformation reaction.